2022
DOI: 10.17584/rcch.2022v16i2.13832
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of nutrients during the formation of star fruit cultivars under different irrigation regimes

Abstract: Nutrient accumulation during the formation of star fruit (Averrhoa carambola) trees can be affected by the water regime and by the cultivar, but the details are not yet known for this species. The aim of this study was to evaluate the nutrient uptake of two star fruit cultivars in the formation phase under two irrigation regimes. The experiment was developed with a completely randomized design, with subdivided plots, with two irrigation levels (with and without irrigation) as plots, and two star fruit cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It should be noted that fertile soil, by itself, is not a guarantee of well-nourished and productive plants, since factors such as soil compaction, interaction among nutrients, water availability in the environment, etc., can compromise the absorption of essential elements. The last condition was observed by Rozane et al (2022), when evaluating the nutrient uptake by two star fruit cultivars (B-10 and Golden Star), with approximately two years of age, under two water regimes (with and without irrigation). The authors concluded that, regardless of cultivar, the greatest nutrient uptake occurred in the irrigated regime.…”
Section: Foliar Diagnosismentioning
confidence: 99%
“…It should be noted that fertile soil, by itself, is not a guarantee of well-nourished and productive plants, since factors such as soil compaction, interaction among nutrients, water availability in the environment, etc., can compromise the absorption of essential elements. The last condition was observed by Rozane et al (2022), when evaluating the nutrient uptake by two star fruit cultivars (B-10 and Golden Star), with approximately two years of age, under two water regimes (with and without irrigation). The authors concluded that, regardless of cultivar, the greatest nutrient uptake occurred in the irrigated regime.…”
Section: Foliar Diagnosismentioning
confidence: 99%